2009
DOI: 10.1038/nchem.255
|View full text |Cite
|
Sign up to set email alerts
|

Carboalumination of a chromium–chromium quintuple bond

Abstract: Bonds are at the very heart of chemistry. Although the order of carbon–carbon bonds only extends to triple bonds, metal–metal bond orders of up to five are known for stable compounds, particularly between chromium atoms. Carbometallation and especially carboalumination reactions of carbon–carbon double and triple bonds are a well established synthetic protocol in organometallic chemistry and organic synthesis. We now extend these reactions to compounds containing chromium–chromium quintuple bonds. Analogous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(99 citation statements)
references
References 47 publications
2
95
1
1
Order By: Relevance
“…Only very few reports on quintuple bond reactivity have appeared in the literature so far. [12] Quintuply bonded bimetallic complexes show a potential for small-molecule activation, particularly on a diatomic platform that can provide from two to eight (in principle even ten) electrons. These complexes feature not just low-valent metal centres, they are also coordinatively highly unsaturated.…”
mentioning
confidence: 99%
“…Only very few reports on quintuple bond reactivity have appeared in the literature so far. [12] Quintuply bonded bimetallic complexes show a potential for small-molecule activation, particularly on a diatomic platform that can provide from two to eight (in principle even ten) electrons. These complexes feature not just low-valent metal centres, they are also coordinatively highly unsaturated.…”
mentioning
confidence: 99%
“…[10] Until now only very few quintuple bond reactivity studies have appeared. [11] Activation of white phosphorus by main group elements [12] and transition metals [13] is an active research area in chemistry. However, bimetallic activation by transition metals is very rare.…”
Section: In Memory Of Kurt Dehnickementioning
confidence: 99%
“…[7] These low-coordinate quintuple-bonded species not only have interesting metal-metal bonding, but also show remarkable reaction chemistry. [8][9][10][11][12][13][14][15][16] Recent studies have indicated that there are strong analogies between the d component of the metal-metal quintuple bonds and the p component of the carbon-carbon multiple bonds. For example, the quintuple bonded molybdenum amidinate dimers [Mo 2 {m-k 2 -RC(N-2,6-iPr 2 C 6 H 3 ) 2 } 2 ] (R = H (1), Ph) [17] react with two equivalents of terminal alkynes to give the first aromatics containing two multiple-bonded dimetal units by a [2+2+2] cycloaddition process, [14] while its chromium analogue [Cr 2 {m-k 2 -HC(N-2,6-iPr 2 C 6 H 3 ) 2 } 2 ] (2) [18] reacts with alkynes to afford [2+2] adducts.…”
mentioning
confidence: 99%
“…[13] These reactivity analogies between p p and d d systems inspired us to explore functionalization of the metal-metal quintuple bonds.…”
mentioning
confidence: 99%